Attractivity of solutions of Riemann–Liouville fractional differential equations - Tao Zhu (Electronic Journal of Qualitative Theory of Differential Equations, 2022)
Some new weakly singular integral inequalities are established by a new method, which generalize some results of this type in some previous papers. By these new integral inequalities, we present the attractivity of solutions for Riemann–Liouville fractional differential equations. Finally, several examples are given to illustrate our main results.